A Study on How Industrial Pharmacists Rank Competences for Pharmacy Practice: A Case for Industrial Pharmacy Specialization - Jeffrey Atkinson; Kristien De Paepe; Antonio Sánchez Pozo; Dimitrios Rekkas; Daisy Volmer; Jouni Hirvonen; Borut Bozic; Agnieska Skowron; Constantin Mircioiu; Annie Marcincal; Andries Koster; Keith Wilson; et al. (MDPI AG, 2016)
This paper looks at the way in which industrial pharmacists rank the fundamental competences for pharmacy practice. European industrial pharmacists (n = 135) ranked 68 competences for practice, arranged into 13 clusters of two types (personal and patient care). Results show that, compared to community pharmacists (n = 258), industrial pharmacists rank competences centering on research, development and production of drugs higher, and those centering on patient care lower. Competences centering on values, communication skills, etc. were ranked similarly by the two groups of pharmacists. These results are discussed in the light of the existence or not of an "industrial pharmacy" specialization.